2014
DOI: 10.3998/ark.5550190.p008.412
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic approaches to asymmetric phthalocyanines and their analogues

Abstract: This review summarizes synthetic strategies for the preparation of asymmetric phthalocyanines and their analogues. Cross-condensation between two phthalonitrile components, crosscondensation between one phthalonitrile and one non-nitrile component, targeted synthesis of AABB-type compounds, the subphthalocyanine ring-expansion method, as well as postmodification approaches on pre-formed symmetric and asymmetric systems, are discussed. Methodologies for targeted preparation of specific types of asymmetric phtha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 195 publications
0
28
0
Order By: Relevance
“…Based on the proposed mechanism, we recognized that our synthetic protocol had the potential to introduce different benzo fragments ( A and B ) around the macrocycle in a regiospecific manner, in addition to the meso functionality (Scheme 1). Such structural control has been long pursued in normal Pc chemistry with only limited advances [9] . In the hybrid series, success would deliver materials that are unavailable in general Pc chemistry, but also offer the opportunity to further exploit the possibilities provided by the meso ‐substituent.…”
Section: Figurementioning
confidence: 99%
“…Based on the proposed mechanism, we recognized that our synthetic protocol had the potential to introduce different benzo fragments ( A and B ) around the macrocycle in a regiospecific manner, in addition to the meso functionality (Scheme 1). Such structural control has been long pursued in normal Pc chemistry with only limited advances [9] . In the hybrid series, success would deliver materials that are unavailable in general Pc chemistry, but also offer the opportunity to further exploit the possibilities provided by the meso ‐substituent.…”
Section: Figurementioning
confidence: 99%
“…In recent years, synthesizing asymmetric Pcs started attracting attention after studies showed that PSs with an amphiphilic substitution pattern have higher activity than their symmetric analogues; while positively charged groups promote interaction with the bacterial cell outer membrane, the hydrophobic part may direct the PS to the interior of the cell. Several strategies for synthesizing asymmetric Pcs have been described in the literature [52] . Using a statistical condensation method, we recently showed that 2,4,6‐tris( N , N ‐dimethylaminomethyl) phenoxy‐substituted ZnPcs bearing none, three or six thiophenyl moieties could be readily synthesized [53] .…”
Section: Molecular Photosensitizersmentioning
confidence: 99%
“…[51] In recent years,s ynthesizinga symmetric Pcs starteda ttracting attention after studies showed that PSs with an amphiphilic substitution pattern have higher activity than their symmetric analogues;w hile positively chargedg roups promote interaction with the bacterial cell outer membrane, the hydrophobic part may directt he PS to the interior of the cell.S everal strategies for synthesizinga symmetric Pcs have been described in the literature. [52] Using as tatistical condensation method, we recently showedthat 2,4,6-tris(N,N-dimethylaminomethyl) phenoxy-substituted ZnPcs bearing none, three or six thiophenyl moieties could be readily synthesized. [53] Upon introducing the thiophenyl groups, the singlet oxygen quantum yield wasi ncreased from 0.61 for 27 b to 0.76 for 28 and 0.81 for 29.F or the first time, we showed that aP S 'sp hotobiological activity depended on the flexibilityo ft he moleculer ather than itsa bility to generate ROS.A ta1mm concentration,l ight activation of 27 b and 28 resulted in a > 5log reduction of viable E. coli with al ight dose of 18 Jcm À2 .W hen 29 was tested under the same conditions, the colony forming units were reduced by < 2log 10 .A tthe same time, the Yoon group published an interesting study showing that an on-quaternized derivativeo f27 b was able to self-assemble into nanodotst hat generate ROS via the Type Im echanism.…”
Section: Zinc(ii)phthalocyaninesmentioning
confidence: 99%
“…Pcs are known for their electrocatalytic behaviour towards many analytes including hydrazine [7, 8]. For many years, symmetrical Pcs have been the subject of many studies owing to the fact that the purification of such molecules is easier relative to their asymmetrical counterparts and the yields thereof are fairly high [9, 10]. Despite all these setbacks, asymmetrical Pcs, particularly the A 3 B analogues, have gained a great deal of traction because they seem to function better than their symmetrical counterparts in certain areas such as non‐linear optics (NLO) [11].…”
Section: Introductionmentioning
confidence: 99%